An Innovative Approach for Environmental Monitoring by Solar Powered Kite - Ishak, Muhammad Irfan; Thakur, Riazul Islam; Kaewpraek, Chila; Boon Kar, Yap; Rahman, Kazi Sajedur; Techato, Kuaanan; Akhtaruzzaman, Md.; Tiong, Sieh Kiong; Amin, Nowshad (International Journal of Integrated Engineering, 2020)
This study investigates the design of a solar powered kite equipped with sensors for any environmental data monitoring, such as, temperature, pressure and so on towards the elevated environment. The developed prototype transforms a traditional kite with a unique design approach that involves the upward height measurement, energy harvesting by solar cells as well as data transmission via wireless network. However, the results from initial monitoring shows only the vertical mapping of ambient temperature as the test case. The developed system can successfully sense and display the temperature data from various height within a certain range as found in the initial investigation. Therefore, upon monitoring various environmental parameters at any cases or during emergency situations using the solar-kite as the simple tool, decision can be made to take appropriate measures against any detrimental changes of the environment by other means.